2007
DOI: 10.1111/j.1440-1754.2007.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating attitudes and behaviours among adolescents in Hong Kong: Prevalence and correlates

Abstract: Disordered eating is prevalent among adolescents in Hong Kong. It remains a significant public health challenge to our community. Prevention programmes targeting youths at the greatest risk should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
0
36
0
6
Order By: Relevance
“…Os principais termos usados para caracterizar a presença de comportamentos de risco para TA foram "risco de transtornos alimentares" 13,[27][28][29][30]34,38,52,60,67,[77][78][79]81,82,88 e "comer transtornado" 35,39,41,[43][44][45][46]48,63,65,68,73,84,86 . Mesmo assim, mais de 60% dos estudos utilizaram outras diversas nomenclaturas e, no contexto do Brasil, observa-se que também não há padronização dos termos.…”
Section: Discussionunclassified
“…Os principais termos usados para caracterizar a presença de comportamentos de risco para TA foram "risco de transtornos alimentares" 13,[27][28][29][30]34,38,52,60,67,[77][78][79]81,82,88 e "comer transtornado" 35,39,41,[43][44][45][46]48,63,65,68,73,84,86 . Mesmo assim, mais de 60% dos estudos utilizaram outras diversas nomenclaturas e, no contexto do Brasil, observa-se que também não há padronização dos termos.…”
Section: Discussionunclassified
“…This is inconsistent to results from other studies indicating that extreme weightcontrol behavior is higher among girls than boys. 8,13,14,42 Studies have found that the perception of being overweight is one reason that adolescents decide to attempt weight loss, regardless of whether they are truly overweight. 26,27 Consistent with results from previous studies, 42,43 this study found that adolescents who perceived their body weight as too fat were more likely to follow an unhealthy diet.…”
Section: Prevalence Of Weight-control Behaviors By Weight-status Permentioning
confidence: 99%
“…9 Unhealthy dieting can also decrease intake of energy and essential nutrients and may be associated with a variety of symptoms including fatigue, anxiety, and constipation and irregular menstrual cycles among girls. 4 The high prevalence of abnormal eating patterns and unhealthy weight-control behaviors in adolescents has become a major public health concern 8,[10][11][12][13] worldwide. These practices have been shown to be related to sociodemographic and personal characteristics of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Yeme bozukluğu, obeziteye neden olan aşırı yemek yeme, yemek yemeyi reddetme, bireyin vejetaryen olması veya bazı psikolojik nedenlerden ötürü yemek yemeyi kısıt-laması, yemek olmayan maddelerin yenilmesi, yenen yemeğin hemen sindirilerek atılması veya karşı konulamaz gece yemek yeme davranışlarının sergilenmesidir (2). Gençlerde yeme bozukluklarının ortaya çıkmasındaki etken, yeme tutumunun özellikle bu dönemde birçok faktörden etkilenmesi olarak görülür (3).…”
Section: Introductionunclassified
“…Cinsiyetin etkisi değerlendirildiğinde, özellikle genç kız-ların erkeklere göre beden imajı ve estetiğe daha fazla önem verdikleri ve yeme bozukluklarına daha eğilimli oldukları görülmektedir. (6). Yeme tutumunu etkileyen diğer faktörler beden kitle indeksi (BKI), beden memnuniyetsizliği ve diyet yapmadır (7)(8)(9).…”
Section: Introductionunclassified